ANALISIS PERBANDINGAN KINERJA KEUANGAN DENGAN METODE CAR ANTARA PT. BRI (Persero) Tbk DAN PT. BNI (Persero) Tbk YANG TERDAFTAR DI BEI - Karimah, Anifatul; Dwiningwarni, SS; Masyhadi, H; Muhajir, Ali (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2018)
Banks are financial institutions that play an important role in the economy of a country. Therefore, the existence of a healthy bank is very necessary. This study aims to compare the financial performance of Indonesian people's banks (BRI) and Indonesian state banks (BNI) based on financial ratio analysis listed on the Indonesia Stock Exchange for the period 2012-2016. The study uses the CAR (Capital Adequacy Ratio) method in which the ratio shows how far all bank assets that contain risks (credit, participation, securities, bills at other banks) are also financed from the bank's own capital funds in addition to obtaining funds from sources sources outside the bank, such as community funds, loans (debts), etc. ... The results of this study indicate that the CAR ratio in BRI is better than that of BNI banks. This proves that the CAR ratio and financial performance at BRI banks are better than BNI banks. Because it can manage capital as well as possible and accommodate the risk of loss. The results also show that BRI is better known to the lower middle class.